Conductance of Carbon Atomic Wire in the Environment of $H_2O$ Molecules (Journal of Atomic and Molecular Sciences, 2010)
The conductance of carbon atomic wire in the environment of $H_2O$ molecules is studied by the non-equilibrium Green functionmethod  based on density functional theory. In particular,  thecarbon wire with seven atoms sandwiched between the Al(100)electrodes is considered. It is found that the transport propertiesare sensitive to the variation of the number and the position of the $H_2O$ molecule adsorbed on the carbon wire. To our surprise, withdifferent positions of a single $H_2O$ molecule on the carbon wire,the equilibrium conductance shows an evident odd-even oscillatorybehavior. For example, the equilibrium conductance  of the  carbonwire becomes bigger when the $H_2O$ is adsorbed on the odd-numberedcarbon atoms; an opposite conclusion is obtained for the $H_2O$ adsorbed on the even-numbered carbon atoms. For the cases of two $H_2O$ molecules, the equilibrium conductance varies largely and thecontribution of the third eigenchannel becomes larger in somespecial configurations. The above behavior is analyzed via thecharge transfer and the density of states (DOS). Reasonableexplanations are presented.